REFLECTION OF ENLIGHTENMENT LITERATURE IN THE WORKS OF ALEXANDER POPE - Ochilova, Nigora Maxmudjanovna; Akhmedova, Ra’no Ashurovna; Nematova, Mohibegim Fazliddinovna (International Journal of Psychosocial Rehabilitation, 2020)
the aesthetic views of Enlightenment literature were valued in that poets and writers served the educational value of art in the interests of the reconstruction of society. Eighteenth-century writers created enlightened political-philosophical novels, philosophical narratives, and dramatic works of a political-moral nature. The ideas of humanism, liberalism, intelligence, and the reconstruction of society through the enlightenment of the people, propagated in the literature of the English Enlightenment of the eighteenth century, are deeply reflected in the poetry and drama of that period.